Identification of a meiosis-specific protein as a member of the class of cancer/testis antigens - Türeci, Özlem (The National Academy of Sciences, 1998)
Little is known about the function of human cancer/testis antigens (CTAs), such as MAGE, BAGE, GAGE, HOM-MEL-40, and NY-ESO-1, the expression of which is restricted to human malignancies and testis. When screening a cDNA expression library enriched for testis-specific representative long transcripts for reactivity with high-titered IgG antibodies from the serum of a patient with renal cell carcinoma, one repeatedly detected antigen, designated HOM-TES-14, turned out to be encoded by the synaptonemal complex protein 1 (SCP-1) gene. SCP-1 is known to be selectively expressed during the meiotic prophase of spermatocytes and is involved in the pairing of homologous chromosomes, an essential step for the generation of haploid cells in meiosis I. Investigation of a broad spectrum of normal and malignant tissues revealed expression of SCP-1 transcripts and antigen selectively in a variety of neoplastic tissues and tumor cell lines. Immunofluorescence microscopy analysis with specific antiserum showed a cell cycle phase-independent nuclear expression of SCP-1 protein in cancer cells. SCP-1 differs from other members of the class of CTA by its localization on chromosome 1 and its frequent expression in malignant gliomas, breast, renal cell, and ovarian cancer. The aberrant expression of SCP-1 in tumors might contribute to their genomic instability and suggests that the functional role of other CTA might also relate to meiosis.